6,7-seco-ent-kauranoids derived from oridonin as potential anticancer agents - Xu, Shengtao; Yao, Hong; Hu, Mei; Li, Dahong; Zhu, Zheying; Xie, Weijia; Yao, Hequan; Wu, Liang; Chen, Zhe-Sheng; Xu, Jinyi (American Chemical Society, 2017)
Structurally unique 6,7-seco-ent-kaurenes, which are widely distributed in the genus Isodon, have attracted considerable attention because of their antitumor activities. Previously, a convenient conversion of commercially available oridonin (1) to 6,7-seco-ent-kaurenes was developed. Herein, several novel spiro-lactone-type ent-kaurene derivatives bearing various substituents at the C-1 and C-14 positions were further designed and synthesized from the natural product oridonin. Moreover, a number of seven-membered C-ring-expanded 6,7-seco-ent-kaurenes were also identified for the first time. It was observed that most of the spiro-lactone-type ent-kaurenes tested markedly inhibited the proliferation of cancer cells, with an IC50 value as low as 0.55 μM. An investigation on its mechanism of action showed that the representative compound 7b affected the cell cycle and induced apoptosis at a low micromolar level in MCF-7 human breast cancer cells. Furthermore, compound 7b inhibited liver tumor growth in an in vivo mouse model and exhibited no observable toxic effects. Collectively, the results warrant further preclinical investigations of these spiro-lactone-type ent-kaurenes as potential novel anticancer agents.